HUKUM ADAT DAN TRADISI PEMILIKAN TANAH DALAM MASYARAKAT ADAT PASER DI KALIMANTAN - Inzaghi Harnadi Yudha Perdana; Franky Alex Shandy; Iva Yuni Susanti; Maharani Hidayah (Pojok Publisher, 2025)
Land occupies a very important position in the life of the Paser customary law community. For the Paser customary community, land is considered an ancestral heritage full of religious values that have been passed down from generation to generation. Cases of disputes with companies and the government and plans to move the nation's capital have created an atmosphere of tension in society. This study aims to examine how the concept of land ownership according to customary law applies in the Paser customary community in East Kalimantan, as well as to examine the form of legal protection for customary land belonging to the Paser tribe, especially in the context of the construction or relocation of the Indonesian Capital City (IKN). The materials used in this study, which uses a literature review research approach, were collected from a number of reliable sources, including books, scientific journals, and related government papers. The results of this study are that customary rights are the collective rights of indigenous peoples to manage and protect land, so that determining customary boundaries is important to prevent conflict, especially to protect Paser customary land rights from the threat of agrarian conflict due to the construction of the IKN. As stated in Paser Regency Regional Regulation No. 14 of 2019, these provisions cover various aspects of customary land ownership, environmental preservation, access to education and health, and cultural protection. The development of the IKN must consider the communal rights of indigenous peoples, and the necessary legal protection includes recognition of customary rights and zoning regulations that respect local culture.